آليات تدخل القاضي الإداري ضد الإدارة الممتنعة عن تنفيذ أحكامه - مولود, حاتم (University of Eloued جامعة الوادي, 2018)
the judicial authority exercises its prerogatives, consisting in removing all kinds of law violations, each time this will be exposed before it, accordingly to the Algerian law. Thus the administrative judge is empowered to examine the legitimacy of decisions and acts done by the administration and say if they really respect the law. The positive role of the administrative judge is, in fact, concretized by his intervention to insure the enforcement of his sentences, regarding his authority to extend the his authority and competence during the hearing of the dispute and even after the adjudicate upon it; which is different from the ordinary judge who abandons the file once the dispute is settled. Contrarily to the administrative judge who intervenes in the implementation phase, by the enforcement mechanisms authorized by the law.
الملتقى الدولي الثامن: التوجيهات الحديثة للقضاء الإداري ودوره في إرساء دولة القانون 06-07 مارس 2018 جامعة الوادي
Keywords: تدخل القاضي الإداري، الإمتناع عن التنفيذ، آليات تنفيذ الأحكام الإدارية